The Application of Translation Theories in Students’ Practice in the Course Theories and Practice of Translation: An Analytical Study - Maharani; Tinur Rahmawati Harahap; Ruth Berlian Sianipar; Nabila Ramadhani Siregar (ETANIC Journal Of English Language Teaching And Applied Linguistics, 2026)
The course Theories and Practice of Translation is a core subject in English Education programs that aims to equip students with theoretical knowledge and practical translation skills. In practice, however, students often encounter difficulties in applying translation theories consistently when translating texts. This study aims to analyze the application of translation theories in students’ translation practices in the Theories and Practice of Translation course at Universitas Graha Nusantara. This research employed a qualitative descriptive approach with an analytical orientation. The participants were undergraduate students of the English Education Study Program who had completed the course. Data were collected through analysis of students’ translation assignments, classroom observations, and semi-structured interviews. The findings show that students applied several translation theories, such as equivalence theory, semantic and communicative translation, and functional approaches, but the application was not always consistent. Many students tended to rely on intuition when facing complex translation problems. Nevertheless, guided practice and reflective discussion helped students improve their theoretical awareness and translation quality. This study concludes that continuous integration of translation theories into practical activities is essential to enhance students’ analytical skills and overall translation competence.